Investigating the Convergence between Actigraphy, Maternal Sleep Diaries, and the Child Behavior Checklist as Measures of Sleep in Toddlers - Bélanger, Marie-Ève; Simard, Valérie; Bernier, Annie; Carrier, Julie (Frontiers in Psychiatry, 2014)
The current study examined associations among actigraphy, maternal sleep diaries, and the parent-completed child behavior checklist (CBCL) sleep items. These items are often used as a sleep measure despite their unclear validity with young children. Eighty middle class families (39 girls) drawn from a community sample participated. Children (M = 25.34 months, SD = 1.04) wore an actigraph monitor (Mini-Mitter® Actiwatch Actigraph, Respironics) for a 72-h period, and mothers completed a sleep diary during the same period. Eighty-nine percent of the mothers and 75% of the fathers also filled out the CBCL (1.5–5). Mother and father CBCL scores were highly correlated. Overall, good correspondence was found between the CBCL filled out by mothers and sleep efficiency and duration derived from maternal sleep diaries (r between −0.39 and −0.25, p ≤ 0.05). Good correspondence was also found between the CBCL filled out by fathers and sleep efficiency as derived from maternal sleep diaries (r between −0.39 and −0.24, p ≤ 0.05), but not with sleep duration (all results were non-significant). Very few correlations between actigraphy and the CLBL scores reached statistical significance. The Bland and Altman method revealed that sleep diaries and actigraphy showed poor agreement with one another when assessing sleep duration and sleep efficiency. However, diary- and actigraphy-derived sleep durations were significantly correlated. Consistent with findings among older groups of children, this study suggests that the CBCL sleep items, sleep diaries, and actigraphy tap into quite different aspects of sleep among toddlers. The choice of which measures to use should be based on the exact aspects of sleep that one aims to assess. Overall, despite its frequent use, the composite sleep score of the CBCL shows poor links to objective measures of sleep duration and sleep efficiency.